2004
DOI: 10.1158/1078-0432.ccr-1117-3
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Responses to Peptides Correlate with Overall Survival in Advanced Cancer Patients Vaccinated with Peptides Based on Pre-existing, Peptide-Specific Cellular Responses

Abstract: Purpose: The aim of this study is to find a laboratory marker for overall survival in advanced cancer patients who were vaccinated with peptides based on pre-existing, peptide-specific CTL precursors in the circulation.Experimental Design: A group of 113 patients with advanced cancer (28 colorectal, 22 prostate, 15 lung, 14 gastric, and 34 other cancers) was enrolled in a Phase I clinical study of peptide vaccination in which peptidespecific CTL precursors of prevaccination peripheral blood mononuclear cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
94
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 30 publications
10
94
0
Order By: Relevance
“…At present, a correlation between the induction of immune responses during various immunotherapy and the clinical outcome of treated patients remains controversial (35)(36)(37)(38). This dispute could be due to the variation of the quality of immunological assays among investigators, variable levels of tumor burden, and the different criteria used for measuring clinical responses by tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a correlation between the induction of immune responses during various immunotherapy and the clinical outcome of treated patients remains controversial (35)(36)(37)(38). This dispute could be due to the variation of the quality of immunological assays among investigators, variable levels of tumor burden, and the different criteria used for measuring clinical responses by tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…35 Other studies reported positive influences on PSA kinetics in patients receiving PSA RNA-transfected DC 7 or tumor lysate-pulsed DC. 27 In an earlier study, objective clinical remissions were observed after vaccination with DC loaded with HLA-A2-restricted PSMA-derived peptide-even in HLA-A2 negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to post-vaccination biomarkers, several factors, including CTL responses, Th1 responses, delayed-type hypersensitivity (DTH) and autoimmunity, have been reported to be associated with clinical responses in some clinical trials (14,15). We have also shown that an increase in peptide-specific IgG and/or CTL responses after PPV is significantly associated with longer OS (11,12). In contrast to such post-vaccination biomarkers, there are currently no validated pre-vaccination prognostic biomarkers widely used.…”
Section: Discussionmentioning
confidence: 80%